Colour variation in immature coffee dried under different dry bulb and dew point temperature conditions (Research, Society and Development, 2020)
This study evaluated colour variation as a function of the drying kinetics of immature coffee subjected to different drying conditions. Additionally, mathematical models were fitted to experimental data for green coffee berries dried in a thin layer under different drying conditions, besides the water reduction rate (WRR) was determined. Each of the drying environments was determined by the combination of three different dry bulb temperatures (Tdb) (35, 40 and 45 °C) and three different dew point temperatures (Tdp) (2.6, 10.8 and 16.2 °C). Coffee (Coffea arabica L.) berries of the Topázio Amarelo variety were collected manually and selectively with initial water content of 2.106 ± 0.05 kg.kg-1 (dry basis, db); they were processed by the dry-processing method and dried to a final water content of 0.124 ± 0.05 kg.kg-1 (db) in a fixed-bed dryer combined with a laboratory air conditioning system (LACS). Following this process, the samples were separated into two parts, one containing beans with black-green and sour defects and the other containing the remaining beans, and the colour was read for each group. For all drying combinations, the Midilli model best fit the experimental data. The lowest WRR was 0.063 kg.kg-1.h-1 and occurred in the combination with the Tdb of 35 °C and Tdp of 16.2 °C. In the portion of coffee without defects, among the treatments performed at the Tdb of 35 °C, the combination with the Tdp of 2.6 °C had the lowest luminance values. For the “a” coordinate, the lowest values were found in the combination of the Tdb of 35 °C and Tdp of 2.6 °C.